Colorectal Cancer in the Elderly - Tan, Kok-Yang. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
As the population ages, clinicians are facing an increasing number of elderly patients with colorectal cancer. Disease management in these patients poses a unique challenge as they have more comorbidities and lower functional reserves. In addition, the treatment goals may differ from those in younger patients. Appropriate management of elderly patients demands a greater understanding of not only the physiological changes but also issues related to the delivery of holistic care. This book discusses in depth the different aspects of management of colorectal cancer in the elderly. After the provision of pertinent background information on the normal physiology of aging, screening and diagnosis are discussed. Subsequent chapters focus on a range of issues associated with the surgical and perioperative care of these patients and with adjuvant treatment and palliative care. Each chapter provides helpful take-home messages in bullet point form, and numerous informative figures and tables are also included. The authors are surgeons, physicians, anesthetists, geriatricians, oncologists, and allied health professionals with extensive experience in the field. This book discusses in depth the different aspects of management of colorectal cancer in the elderly. After the provision of pertinent background information on the normal physiology of aging, screening and diagnosis are discussed. Subsequent chapters focus on a range of issues associated with the surgical and perioperative care of these patients and with adjuvant treatment and palliative care. Each chapter provides helpful take-home messages in bullet point form, and numerous informative figures and tables are also included. The authors are surgeons, physicians, anesthetists, geriatricians, oncologists, and allied health professionals with extensive experience in the field.